MODEL COOPERATIVE LEARNING PADA PELAJARAN AKIDAH AKHLAK DI MTSN 2 SIDOARJO: IMPLEMENTASI TEORI BELAJAR KONSTRUKTIVISME VYGOTSKY - Agustin, Fia Ayu Putri; Ningrum, Annisa Eka Ayu Cahya; Khotimah, Siti Khorriyatul (Universitas Islam Lamongan, 2024)
This study explores the implementation of the cooperative learning model in the Akidah Akhlak subject at MTsN 2 Sidoarjo and how Vygotsky's constructivist theory is applied in this context. Cooperative learning emphasizes collaboration among students to achieve common learning goals, while Vygotsky's constructivism highlights the importance of social interaction and scaffolding in the learning process. The research method used is qualitative with a case study approach, collecting data through classroom observations, interviews with teachers and students, and document analysis. The findings show that cooperative learning has a positive impact on students' understanding and practice of Akidah Akhlak values, with social interactions in small groups helping students construct a more complex understanding of the material. The application of Vygotsky's constructivist theory is evident in the use of scaffolding by teachers to guide students in reaching the Zone of Proximal Development (ZPD), providing initial support that is gradually reduced as students gain independence. This study concludes that the cooperative learning model, supported by Vygotsky's constructivist principles, is effective in enhancing the quality of Akidah Akhlak education at MTsN 2 Sidoarjo.